LITERATURE ANALYSIS ON THE INFLUENCE OF LEADERSHIP STYLES ON JOB SATISFACTION THROUGH ORGANIZATIONAL CULTURE - Muhammad Maulana Ibrahim; Budi Eko Soetjipto; Ludi Wishnu Wardana (RADJA PUBLIKA, 2025)
The aim of this study is to systematically investigate the influence of transformational, transactional, and servant leadership styles on employee job satisfaction, with organizational culture serving as an intervening variable. A Systematic Literature Review (SLR) method was adopted, sourcing literature from Scopus-indexed journals (Q1–Q4) published between 2020 and 2025. The analysis employed descriptive, thematic, and content-based approaches. The results reveal that transformational and servant leadership styles significantly enhance affective and psychosocial dimensions of job satisfaction, while transactional leadership is more effective within structured organizational environments. Furthermore, organizational culture functions as a strategic mediator that strengthens these relationships. These findings highlight the critical importance of aligning leadership styles with organizational culture to foster inclusive, sustainable leadership practices and contribute to the realization of Sustainable Development Goals (SDGs), particularly those related to decent work and economic growth.